TRANSFORMASI SISTEM PENEMUAN HUKUM: IMPLIKASI DAN DAMPAKNYA TERHADAP HUKUM DI INDONESIA - Kurniawan, Fuji (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The legal discovery syetem is a unity consisting of methods, sources, subjects, flows and processes of how to find the law as referred to in Law Number 48 of 2009 concerning Judicial Power which has provided guideliness of the subject of legal discovery in Indonesia. This journal discusses the changes in the legal discovery system in Indonesia. This journal examines how judges and other subject of legal discovery feel the impact of changes in the legal system in Indonesia which initially used a heternonomous legal discovery system starting to shift to a autonomous legal discovery system. This study also discusses the implications of the change in the legal system as well as the impact of the change in the legal system in Indonesia. This journal uses a normative juridical approach to equate the guidelines for finding law in the law with how the legal discovery system applies in reality.